«Within Sanction Regime»: Problems and Perspectives of Russian Economic and Political Development. The Papers of the “Round Table” of the Lecturers and Students of the Peoples’ Friendship University of Russia - Denis Olegovich Matveenkov (RUDN Journal of Political Science, 2016)
The paper comprises the materials of the “round-table” “Within sanctions regime: problems and perspectives of Russian economic and political development” which was organized by the chair of the comparative politics of the Peoples` Friendship University of Russia (PFUR) and took place on February 20. 2016 on the faculty of the humanities and social sciences. Among the questions discussed within the “round table” were economic and political aftermaths of the sanctions imposed on Russia by the West and Russian countersanctions against the EU, USA and the further perspectives of Russian economic and political development, cooperation with the West. Among the participants of the “round-table” were the lecturers and the students of the political department of the PFUR, the students of the faculty of applied political sciences of the National Research University of Higher School of Economics as well as political experts.